Water Vapor Permeability of edible starch based films - Bertuzzi, Maria Alejandra (2007)
Water transport in edible films of starch based products is a complex phenomenon due to the strong interaction of sorbed water molecules with polymeric structure of starch. Water sorption isotherms on high amylose starch based films are highly non linear in the range studied (5-45 °C). So permeability is usually affected by a number of parameters such as temperature, film thickness and plasticizer content. This knowledge is required to simulate and predict transport patterns. In the present contribution water vapor permeability (WVP) of high amylose corn starch (HACS) films, prepared in our laboratory, was determined following ASTM E-96 procedure. WVP increases as temperature increases between 5 and 40 °C and observed results can be correlated with an Arrhenius-type expression. Activation energy of WVP for the starch film investigated is 5.61 kJ/mol and values of WVP ranged between 2 × 10-10 and 1 × 10-9 g m-1 s-1 Pa-1. It is also shown a direct relation between WVP with plasticizer content and film thickness. These observations could be explained in terms of variations in the number of potential intermolecular interactions in the film structure. © 2006 Elsevier Ltd. All rights reserved.